2018
DOI: 10.1039/c8sc03480j
|View full text |Cite
|
Sign up to set email alerts
|

Carbene-catalyzed enantioselective oxidative coupling of enals and di(hetero)arylmethanes

Abstract: An N-heterocyclic carbene-catalyzed direct oxidative coupling of enals and di(hetero)arylmethanes allows for quick access to optical pure benzimidazole-fused lactams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 55 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…This catalytically generated intermediate can be formed from NHCs upon addition to various α,β-unsaturated aldehydes or acid derivatives (Scheme ). The interception of this intermediate with various bisnucleophiles result in the formation of five- to seven-membered cyclic compounds via [3 + 2], [3 + 3], and [3 + 4] annulations . In the majority of the cases, the carbon-centered nucleophiles add to the β-position of this intermediate in a Michael fashion, followed by the cyclization, to afford the desired products.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This catalytically generated intermediate can be formed from NHCs upon addition to various α,β-unsaturated aldehydes or acid derivatives (Scheme ). The interception of this intermediate with various bisnucleophiles result in the formation of five- to seven-membered cyclic compounds via [3 + 2], [3 + 3], and [3 + 4] annulations . In the majority of the cases, the carbon-centered nucleophiles add to the β-position of this intermediate in a Michael fashion, followed by the cyclization, to afford the desired products.…”
mentioning
confidence: 99%
“…Based on the literature reports, and the mechanism of the related [3 + 3] annulations catalyzed by NHCs, a tentative mechanism of the reaction is proposed (Scheme ). The initially formed carbene from the chiral triazolium salt undergoes nucleophilic attack on 2-bromoenal, followed by a rapid proton transfer results in the formation of the nucleophilic Breslow intermediate ( I ). , The elimination of bromide from intermediate I generates the key α,β-unsaturated acylazolium intermediate ( II ).…”
mentioning
confidence: 99%
“…Applying the oxidative NHC catalysis strategy, enantioselective synthesis of benzimidazole fused lactams 77 was achieved by oxidative coupling of enals 75 with di(hetero)arylmethanes 76 (Scheme 20). [46] They postulated that the product formation was achieved by two concurrent reaction pathways. The first pathway was through the formation of well‐established α , β ‐unsaturated azolium ester intermediate 78 under oxidative NHC catalysis.…”
Section: Figurementioning
confidence: 99%
“…More importantly, in this reaction, not only carbon-heteroatom bonds were generated but also a novel carbon-carbon bond was formed ( Figure 16). In 2018, Chi et al reported the enantioselective NHC-catalyzed oxidative coupling of enals and di(hetero)arylmethanes ( Figure 17) [65]. In one of the proposed mechanisms, there occurs a Claisen rearrangement or 1,4-addition, between the generated acylazolium and di(hetero)arylmethane derivative.…”
Section: Oxidative Nhc Catalysismentioning
confidence: 99%